When birth comes early: Effects on nephrogenesis. Issue 3 (25th February 2013) - Black, Mary Jane; Sutherland, Megan R; Gubhaju, Lina; Kent, Alison L; Dahlstrom, Jane E; Moore, Lynette
Abstract Preterm birth (birth prior to 37 completed weeks of gestation) may occur at a time when the infant kidney is very immature and nephrogenesis is often ongoing. In autopsied preterm human kidneys and in a baboon model of preterm birth it has been shown that nephrogenesis continues after preterm birth, with a significant increase in the number of glomerular generations and number of nephrons formed within the kidney after birth. Of concern, however, morphologically abnormal glomeruli (with a cystic Bowman's space) are often observed; the abnormal glomeruli are only located in the outer renal cortex, suggesting that it is the recently formed glomeruli (perhaps those formed in the extra‐uterine environment) that are affected. The proportion of abnormal glomeruli within the renal cortex differs between infants with some kidneys appearing normal whereas others are severely affected. This suggests that it may be haemodynamic factors and/or factors in the neonatal care of the infant that lead to the glomerular abnormalities. Indeed, the haemodynamic transition at birth where there is a marked increase in systemic blood pressure and renal blood flow are likely to lead to injury of glomerular capillaries, although further studies are required to elucidate this. In order to optimize renal health at the beginning of life in the preterm infant, it is imperative in future studies to gain an understanding of the causes of the glomerular abnormalities in the preterm neonate.